2017
DOI: 10.3340/jkns.2016.0303.018
|View full text |Cite
|
Sign up to set email alerts
|

Adult Patients with Congenital Muscular Torticollis Treated with Bipolar Release : Report of 31 Cases

Abstract: ObjectiveWe assessed the surgical results of bipolar release in 31 adult patients with uncorrected congenital muscular torticollis (CMT) and more than 12 months of follow-up.MethodsThirty-one patients underwent a bipolar release of the sternocleidomastoid muscle (SCM) and were retrospectively analyzed. The mean follow-up period was 14.9 months (range, 12–30). The mean age at time of surgery was 30.3 years (range, 20–54). Patients were evaluated with a modified Lee’s scoring system, cervicomandibular angle (CMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 24 publications
(57 reference statements)
0
22
0
Order By: Relevance
“…Best outcomes are obtained between 1 to 4 years of age group. After 5 years of age, the efficacy of surgery is reduced due to irreversible craniofacial deformity [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Best outcomes are obtained between 1 to 4 years of age group. After 5 years of age, the efficacy of surgery is reduced due to irreversible craniofacial deformity [7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…The outcomes in this series were assessed using the cervicalmandibular angle (CMA) and an adapted version of the modified Lee’s criteria. [ 11 ] The CMA was calculated using radiological head tilt, defined as the angle between a line across the upper margin of the C7 vertebral body and another line that connects the inferior margins of the mandibular angles, as illustrated by Lee et al . [ 11 ]…”
Section: Methodsmentioning
confidence: 99%
“…[ 2 , 14 ] However, literature regarding neglected cases of CMT in adolescent patients is sparse. [ 11 , 17 , 18 ] Because most of these cases are successfully treated in infancy, CMT reports in older patients are scares, and therefore, the optimal surgical treatment is controversial. Surgical approaches include unipolar sternocleidomastoid release, bipolar sternocleidomastoid release with or without Z-plasty, selective denervation, and dorsal cord stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…Side effects include cosmetic changes associated with permanent somatosensory loss or dysesthesia, scarring, or muscle atrophy. 43 An intrathecal baclofen pump might be another treatment option. Baclofen, an agonist of the gamma-aminobutyric acid type B receptor, blocks the release of this excitatory neurotransmitter by interfering with voltage-gated calcium channels.…”
Section: Surgical Strategies For Cervical Deformities and Case Illustmentioning
confidence: 99%
“…In another study, Kim et al [ 42 ] reported significant improvement in radiological parameters such as the cervicomandibular angle and Cobb angle in 87 cervicothoracic scoliosis patients with congenital muscular torticollis. Side effects include cosmetic changes associated with permanent somatosensory loss or dysesthesia, scarring, or muscle atrophy [ 43 ].…”
Section: Surgical Strategies For Cervical Deformities and Case Illustmentioning
confidence: 99%